Impaired acquisition of conditioned taste aversion memory induced by isoflurane is accompanied with calcineurin activation and Egr-1 down-regulation in amygdala in rats. (21st October 2015) - Wang, Sensen; Zhuang, Lei; Yang, Xiaoxuan; Li, Qiang; Xue, Qingsheng; Luo, Yan; Zhang, Fujun; Yu, Buwei
Highlights: Isoflurane exposure disrupted the establishment of aversion memory in rats. Calcineurin activation and Egr-1 down-regulation may contribute to the isoflurane induced impairment of CTA memory acquisition. Isoflurane preconditioning may prevent negative emotional memory of traumatic events. Abstract: Compared to neutral memory, emotional memory is extremely strong and persistent immediately after acquisition, therefore it may recruit specific mechanisms during acquisition. The calcineurin-dependent mechanisms engaging early growth response 1 (Egr-1) have been proved to determine the strength of emotional memory during establishment. Isoflurane, a widely used inhalation anesthetic, can interfere with the acquisition of emotional memory. We hypothesized that isoflurane impairs the acquisition of conditioned taste aversion (CTA) memory in rats and the Egr-1 expression regulation via calcineurin (CaN) and ERK signaling pathway is involved in isoflurane-induced repression of CTA memory. To examine this, we investigated the influence of isoflurane on CTA memory and the expression and activity of CaN, the phosphorylation level of ERK and the expression of Egr-1 in amygdala in response to CTA training in rats. The results showed that isoflurane exposure (1.5%, 2 h) before training impaired the acquisition of CTA memory in rats. Isoflurane exposure increased the CaN activity and decreased the p-ERK and Egr-1 in amygdala in rats. These findings suggest that isoflurane can disrupt the establishment of aversion memory, and CaN activation associating with p-ERK and Egr-1 down-regulation may contribute to the isoflurane induced impairment of aversion memory acquisition.